El epifenomenismo y la filosofía de Schopenhauer - Anselmo-Rivera, Giancarlo (2024)
This article offers an introductory exposition on the relationship between the philosophical thesis of epiphenomenalism and Schopenhauer's philosophy regarding the problem of the mind-body relationship. The most important notions are presented in a summarized manner, which allows the general reader to have an approach towards understanding this problem. On the one hand, contemporary authors who address epiphenomenalism have been considered; on the other hand, to obtain a general vision of Schopenhauer's philosophy and relate it to the topic, the most important concepts from his works have been selected. The examination of these contents allows us to establish a relationship between both proposals and, in turn, invites us to reflect on the possible preponderance of the biological component over reason.